1998
DOI: 10.2527/1998.7641027x
|View full text |Cite
|
Sign up to set email alerts
|

Beef customer satisfaction: role of cut, USDA quality grade, and city on in-home consumer ratings.

Abstract: An in-home beef study evaluated consumer ratings from moderate-to-heavy beef users as influenced by cut (top loin, top sirloin, and top round steaks), USDA quality grade (Top Choice, Low Choice, High Select, and Low Select), and city (Chicago, Houston, Philadelphia, and San Francisco). Consumers (n = 2,212) evaluated each steak for overall like (OLIKE), tenderness (TEND), juiciness (JUIC), flavor desirability (DFLAV), and flavor intensity (IFLAV) using 23-point hedonic scales (23 = like extremely, extremely te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(94 citation statements)
references
References 11 publications
3
86
1
4
Order By: Relevance
“…Previous research indicates as quality grade increases, the palatability traits of juiciness, flavor, and tenderness increase for consumer and trained panelists (Neely et al, 1998;Acheson et al, 2014;Corbin et al, 2015). Furthermore, prior research indicates that as quality grade increases, the percentage of samples rated acceptable by consumers for all palatability traits also increases (Behrends et al, 2005;Corbin et al, 2015;Tatum, 2015;).…”
Section: Quality Treatmentmentioning
confidence: 99%
“…Previous research indicates as quality grade increases, the palatability traits of juiciness, flavor, and tenderness increase for consumer and trained panelists (Neely et al, 1998;Acheson et al, 2014;Corbin et al, 2015). Furthermore, prior research indicates that as quality grade increases, the percentage of samples rated acceptable by consumers for all palatability traits also increases (Behrends et al, 2005;Corbin et al, 2015;Tatum, 2015;).…”
Section: Quality Treatmentmentioning
confidence: 99%
“…flavour, juiciness, tenderness). Research with US consumers who were characterised as 'frequent beef users' revealed that their overall perceptions of the 'taste' of beef are associated with those of the three primary sensory attributes -flavour, juiciness and tenderness (Neely et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Beef palatability is determined by tenderness, juiciness and flavour (Neely et al, 1998). Flavour desirability differences are related to the amount and composition of intramuscular fat (IMF; Fisher et al, 2000).…”
Section: Introductionmentioning
confidence: 99%